RANCANGAN MONITOR KEJERNIHAN AIR DENGAN SENSOR TURBIDITY PADA BAK PENJERNIHAN DI UNIT WATER TREATMENT PLANT BANDAR UDARA INTERNASIONAL SUPADIO - M.B. Yusuf Aviantara; KGS.M.Ismail; Suse Lamtiar S (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
Pontianak Supadio International Airport is one of the airports that provide air transportation services under the management of Angkasa Pura 2. Supadio Airport has a water treatment system to meet all airport water needs. Raw water from the Anak Kapuas River is channeled to the processing basin in the Water Treaetment Plant. The entire water in the reservoir is supplied from a water treatment plant that has been processed to obtain suitable work. However, the purification process and the level of clarity of the water in the purification bath are not properly monitored, resulting in the technician being less efficient. And the final result of the purification process is not necessarily in accordance with the predetermined standard of clean water. Therefore, the presence of a water clarity monitoring system using a Turbidity sensor that directly measures water clarity and displays clarity levels on the screen will improve the technician's performance. With this monitoring system will also get a measured level of water clarity. Thus it can be seen whether the results of the water purification process have met the clear water standards that are in accordance with Indonesia's national standards.